Basic Stata graphics for economics students - Kevin Denny (University College Dublin, UCD School of Economics, 2018)
This paper provides an introduction to the main types of graph in Stata that economics students might need. It covers univariate discrete and continuous variables, bivariate distributions, some simple time plots and methods of visualising the output from estimating models. It shows a small number of the many options available and includes references to further resources.
Keywords: A2; C87; Y10; 330; Stata; graphics; data visualization